Crab Mentality Syndrome in a Public Hospital: Employee Perspectives (Third Sector Social Economic Review, 2026)
This study explores the work experiences of employees from different occupational groups in a public hospital through the lenses of crab bucket syndrome, job crafting, career well-being, employee loyalty, and talent management. Adopting a qualitative phenomenological design, the research drew on semi-structured interviews with 29 participants selected through purposive sampling: 9 physicians, 5 residents, 5 nurses, 5 administrative staff members, and 5 support service workers. Data were analyzed using thematic analysis, supported by MAXQDA. The findings reveal that employees often experience silent competition, devaluation of effort, and reluctance to stand out when success makes them more visible. At the same time, they actively try to create meaning in their work by linking tasks to broader purposes, planning and organizing their workload, communicating effectively, and introducing small improvements. Results further show that career well-being is shaped by the tension between professional development and emotional exhaustion. Employee loyalty is strengthened by job security, belonging, and public service motivation, yet weakened by heavy workload and lack of appreciation. Regarding talent management, participants acknowledged in-service training opportunities but emphasized that institutional support remains largely general rather than individualized. Overall, working life in public hospitals emerges as relational, emotional, and meaning-centered in everyday professional practice.Keywords: public hospital, crab bucket syndrome, job crafting, career well-being, employee loyalty, talent management
Keywords: public hospital, crab bucket syndrome; job crafting; career well-being; employee loyalty; talent management